Know Thy Anemone: A Review of Threats to Octocorals and Anemones and Opportunities for Their Restoration - Steinberg, Rosemary Kate; Dafforn, Katherine A.; Ainsworth, Tracy; Johnston, Emma L. (Frontiers in Marine Science, 2020)
In studies of habitat-forming species, those that are not spatially dominant are often considered ‘non-primary’ habitat and may be overlooked. This is despite the fact that minority habitat formers can provide critical complexity, food, and other services that underpin ecosystem biodiversity. Octocorals and anemones are found in marine and estuarine habitats across all climate zones. Despite their potentially important ecological roles, to date there have been few studies of their specific threats and stressors or attempts at their restoration. Here we review studies of the ecology of octocorals and anemones with a focus on threats and restoration. We identify many threats including habitat damage, collection and trade, disease, predation, pollution, and the most wide-spread – climate change. While evidence suggests that some octocorals and anemone populations may be more resilient to disturbances than stony corals because they often recruit and grow quickly, resilience is not guaranteed. Instead, resilience or susceptibility within this large group is likely to be site and species specific. We find that the loss of octocorals and anemones has been difficult to quantify as most species have no hard structures that remain following a mortality event. Only through long-term monitoring efforts have researchers been able to document change in these populations. Due to the increasing extent and severity of human impacts in marine ecosystems, restoration of habitat forming species is becoming increasingly necessary after disturbance events. To illustrate the challenges ahead for octocoral and anemone restoration, we present two examples of ongoing restoration efforts assessed against the International Standards for the Practice of Ecological Restoration. Restoration planning and implementation progress are documented for the Mediterranean red coral Corallium rubrum and the temperate Australian cauliflower soft coral, Dendronephthya australis. This review and the detailed case studies demonstrate that while some octocorals and anemones can provide resilient habitat within reef systems, a greater research focus on their ecology, threats, and restoration potential is urgently required.